Efeitos da suplementação de taurina sobre tecido adiposo de ratos obesos treinados - Martiniano, Ana Carolina de Almeida [UNESP] (2014)
Pupose: The objective of this study was to evaluate the effects of taurine supplementation in adipose tissue of obese trained mice. Methods: Male Wistar mice were fed with control or hypercaloric diet to induce obesity, and divided into 4 groups: control (CT, control diet, n =6); sedentary (SD, high calorie diet, n= 6); taurine sedentary (SDTAU, high calorie diet with taurine supplementation, n=6); trained (TR, high calorie diet and physical exercise, n=6), taurine trained (TRTAU, high calorie diet with taurine supplementation and physical exercise, n=6). Results: A significant increase in the weight of animals in SD and SDTAU groups compared to groups TR and TRTAU. It is observed that the groups that were supplemented with taurine (SDTAU and TRTAU) showed a significant increase in the blood taurine concentration. The total area of the animals SDTAU group was 132 % higher compared to TRTAU group (p< 0.0073). Regarding fat area was observed significant difference in SDTAU group when compared with to the trained groups associated or not with taurine supplementation. SDTAU and the SD group showed greater weight of epididymal fat (p< 0.0001), while the lowest value was observed in TRTAU group. Regarding the size of adipocytes groups there was significant statistically difference between them. Conclusion: Based on the results presented, it can be concluded that eight weeks of supplementation with taurine associated with exercise was able to reduce visceral fat and decrease the weight of epididymal fat. However, taurine supplementation with and without exercise have not caused changes in the size of the adipocyte.